2020
DOI: 10.1088/1742-6596/1422/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

The development of physics modules based on madihin culture to train kayuh baimbai character

Abstract: The unavailability of the physics module containing local wisdom of South Kalimantan and can trace the character become the background of this research. Therefore, the researcher conducted research and development of physics module on subject vibration, waves, and sounds of madihin culture to train kayuh baimbai character. This study aimed to describe the feasibility of physics modules based on the validity, practicality, effectiveness, and achievement of kayuh baimbai. This study was a research and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
1
5
0
7
Order By: Relevance
“…This was conveyed by Hartini, Firdausi, et al (2018) in their study which showed that module effectiveness increased because students were more motivated by the module that presented the application of learning material in the form of pictures. The application of physics learning based on local wisdom effectively used in the learning process (Selvia et al, 2017;Wati et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This was conveyed by Hartini, Firdausi, et al (2018) in their study which showed that module effectiveness increased because students were more motivated by the module that presented the application of learning material in the form of pictures. The application of physics learning based on local wisdom effectively used in the learning process (Selvia et al, 2017;Wati et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research also stated that local wisdom-based modules could be used to develop character and build students' character to suit cultural values. Oktaviana, Hartini, & Misbah, 2018;Wati, Putri, Misbah, Hartini, & Mahtari, 2020). In addition, Zainuddin & Misbah (2020) stated that the use of modules that were integrated with local wisdom could be used in the learning process because students could understand local knowledge and wisdom, so that students get direct learning experiences with the conditions and culture in the surrounding environment.…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa penelitian menunjukkan bahwa pembelajaran berbasis kearifan local memudahkan siswa memahami materi ajar sehingga dapat meningkatkan hasil belajar fisika (Misbah, Hirani, Annur, Sulaeman, & Ibrahim, 2020;Oktaviana, Hartini, & Misbah, 2017;Mustika Wati, Hartini, Misbah, & Resy, 2017). Selain itu, juga dapat melatih karakter siswa (Hartini, Firdausi, Misbah, & Sulaeman, 2018;Resy, Wati, & Misbah, 2021;M Wati et al, 2020). Menurut Kusmaryono dalam (Wandari et al, 2018) pembelajaran matematika dengan mengangkat budaya lokal merupakan salah satu konsep belajar kreatif yang menghasilkan pembelajaran yang menyenangkan dan bermaknaa karena terdapat konteks nyata yang dijadikan ilmu.…”
Section: Pendahuluanunclassified